Getty Museum - Old masters painting room - Remi Mathis (Wikimedia Commons, 2011)
Notice iconographique issue de Wikimedia Commons. Titre: Getty Museum - Old masters painting room. Room E 202 East Wing of Getty Center: French and Flemish paintings 1600 - 1700, above from left Venus and Adonis by Simon Vouet (1590 - 1649)
Licence Creative Commons Attribution-Share Alike 3.0 via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons